High Prevalence of Anal High-Grade Squamous Intraepithelial Lesions, and Prevention Through Human Papillomavirus Vaccination, in Young Men Who Have Sex With Men Living With Human Immunodeficiency Virus. (15th May 2021) - Palefsky, Joel M; Lensing, Shelly Y; Belzer, Marvin; Lee, Jeannette; Gaur, Aditya H; Mayer, Kenneth; Futterman, Donna; Stier, Elizabeth A; Paul, Mary E; Chiao, Elizabeth Y; Reirden, Daniel; Goldstone, Stephen E; et al.
Abstract: Background: Men who have sex with men (MSM) are at high risk for human papillomavirus (HPV)–related anal cancer. Little is known about the prevalence of low-grade squamous intraepithelial lesions (LSILs) and the anal cancer precursor, high-grade squamous intraepithelial lesions (HSILs), among young MSM with HIV (MSMLWH). HPV vaccination is recommended in this group, but its safety, immunogenicity, and protection against vaccine-type HPV infection and associated LSILs/HSILs have not been studied. Methods: Two hundred and sixty MSMLWH aged 18–26 years were screened at 17 US sites for a clinical trial of the quadrivalent (HPV6, 11, 16, 18) HPV (qHPV) vaccine. Those without HSILs were vaccinated at 0, 2, and 6 months. Cytology, high-resolution anoscopy with biopsies of lesions, serology, and HPV testing of the mouth/penis/scrotum/anus/perianus were performed at screening/month 0 and months 7, 12, and 24. Results: Among 260 MSMLWH screened, the most common reason for exclusion was detection of HSILs in 88/260 (34%). 144 MSMLWH were enrolled. 47% of enrollees were previously exposed to HPV16. No incident qHPV type–associated anal LSILs/HSILs were detected among men naive to that type, compared with 11.1, 2.2, 4.5, and 2.8 cases/100 person-years for HPV6, 11, 16, 18–associated LSILs/HSILs, respectively, among those previously exposed to that type. qHPV was immunogenic and safe with no vaccine-associated serious adverse events. Conclusions: 18–26-year-old MSMLWH naive to qHPV vaccine types were protected against incident qHPV type–associated LSILs/HSILs. Given their high prevalence of HSILs, there is an urgent need to vaccinate young MSMLWH before exposure to vaccine HPV types, before initiating sexual activity, and to perform catch-up vaccination. Abstract : A high proportion of 18-26 year-old men-who-have-sex-with-men-living-with-HIV screened for a quadrivalent HPV (qHPV) vaccine trial had anal low-grade/high-grade squamous intraepithelial lesions (LSIL/HSIL). Vaccinees naive to qHPV types were protected against incident qHPV type-associated-LSIL/HSIL. Vaccination before sexual initiation is critically important.